E.coli O157: H7 and Foodborne Illness - Pesaresi Penner, Karen; Phebus, Randall (My University, 1999)
This publication contains information about E. coli and Foodborne Illness.
MF2138_1999_03
Keywords: MF2138; Health and Safety; MF